On Some SEIRS Epidemic Models (Journal of Nonlinear Modeling and Analysis, 2024)
We discuss a few variations of the SEIRS epidemic model. Howbasic dynamical properties of the models can be derived by using some toolsof the computer algebra system Mathematica is shown, and how invariantsurfaces of the system can be found by using computer algebra system Singularis explained. Some numerical simulations are presented as well.